A Feeling for Systems Development Work: - Design of the ROSA Project - Bødker, Susanne; Greenbaum, Joan (DAIMI Report Series, 1988)
This article is based on the design of a research project that will look at intuition, learning processes, language and roles in the development of computer systems. The research project, called ROSA (a Danish acronym for Roles and Cooperation in Systems Development) grew out of our interest in the informal working practices among systems developers, because it is these informal working relationships that are most often overlooked in research about computer science methods and tools. The project applies a gender perspective to look at the informal work relations of systems developers. The concept of a gender perspective means that we do not intend to look for, or prove, the existence of differences between men and women, but rather to use gender awareness to ’’listen to’’ and get a ’’feeling for’’ how systems developers work together. Our research methods are interdisciplinary and based on action-oriented, participatory methods that help system developers reflect on their own working practices.